Acceleration to advanced children villages through the forum of village children by utilizing the free time, Telagah village's, Sei Bingai sub-district, Langkat district - Siregar, Hairani; Nasution, Eva Syahfitri (Talenta Publisher, 2020)
One of the national policies issued by the government to provide the fulfillment of children's rights is a Child Friendly City / District (KLA). KLA integrates development resources to fulfill children's rights. The birth of the KLA policy is expected to create families, communities and governments who love children. Children get rights and grow well. The fulfillment of children's rights is described in five clusters. One of the sub-clusters in cluster four is the use of free time. Therefore, each village is expected to form a village children forum, as a forum for children to play a role in development. The Assisted Village Program with the sub-topic Acceleration Towards a Child-Friendly Village through the Formation of Village Children Forum with the Use of Free Time in Telagah Village, Sei Bingai District, Langkat Regency has been implemented on July 2, 2020. The things that have been implemented are the formation of a children's forum and having activities such as playing traditional games and training in traditional dances. Village children already have very positive activities outside of school activities that are able to keep children from doing bad things.